Slum or Arcadia? Hungary as “Other Space” in Imre by Edward Prime-Stevenson - Bojti, Zsolt (Hungarian Journal of English and American Studies, 2020)
This essay substantiates the reasons why Edward Prime-Stevenson’s novelette, Imre (1906), which is considered to be the first openly gay novel in English with a happy ending, is set in an imaginary Budapest called Szent-Istvánhely. The paper suggests that there is a list of references to Hungary in late-Victorian gay literature that Prime-Stevenson builds upon. Another common element in these works is that the location, more specifically, the city landscape, plays an important role that maps the gay city and reflects on the English slumming culture in the East End. The paper substantiates the claim that Prime-Stevenson’s fictional Budapest functions as a Foucauldian heterotopias, which can juxtapose and reconcile oppositions coming from associations with Western and Eastern cultures, the slum and an Arcadia, respectively. (ZsB)